Prevalent CD8(+) T cell response against one peptide/MHC complex in autoimmune diabetes - Anderson, Brad (The National Academy of Sciences, 1999)
Spontaneous autoimmune diabetes in nonobese diabetic (NOD) mice is the result of a CD4(+) and CD8(+) T cell-dependent autoimmune process directed against the pancreatic beta cells. CD8(+) T cells play a critical role in the initiation and progression of diabetes, but the specificity and diversity of their antigenic repertoire remain unknown. Here, we define the structure of a peptide mimotope that elicits the proliferation, cytokine secretion, differentiation, and cytotoxicity of a diabetogenic H-2K(d)-restricted CD8(+) T cell specificity (NY8.3) that uses a T cell receptor α (TCRα) rearrangement frequently expressed by CD8(+) T cells propagated from the earliest insulitic lesions of NOD mice (Vα17-Jα42 elements, often joined by the N-region sequence M-R-D/E). Stimulation of splenic CD8(+) T cells from single-chain 8.3-TCRβ-transgenic NOD mice with this mimotope leads to preferential expansion of T cells bearing an endogenously derived TCRα chain identical to the one used by their islet-associated CD8(+) T cells, which is also identical to the 8.3-TCRα sequence. Cytotoxicity assays using islet-derived CD8(+) T cell clones from nontransgenic NOD mice as effectors and peptide-pulsed H-2K(d)-transfected RMA-S cells as targets indicate that nearly half of the CD8(+) T cells recruited to islets in NOD mice specifically recognize the same peptide/H-2K(d) complex. This work demonstrates that beta cell-reactive CD8(+) T cells mount a prevalent response against a single peptide/MHC complex and provides one peptide ligand for CD8(+) T cells in autoimmune diabetes.